THE EFFECT OF RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) AND EARNINGS PER SHARE (EPS) ON STOCK PRICES IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2020 - Eka Travilta Oktaria; Siti Nur Arifa (Universitas Putera Batam, 2022)
This investigation intends to examine the impact of Return On Assets (ROA), Return On Equity (ROE) and Earnings Per Share (EPS) on stock costs in food and refreshment organizations recorded on the Indonesia Stock Exchange (IDX) in 2016-2020. The example choice utilized purposive testing technique, to acquire 11 organizations with 5 periods. The information investigation procedure utilized the traditional supposition test, different straight relapse test, the coefficient of assurance test (R2) and speculation testing to decide the impact of the free factor on the reliant variable. The outcomes showed that (1) the various straight relapse condition Y = 5.858 + 0.018 (X1) + 0.071 (X2) + 0.003 (X3) + e. (2) The worth of the coefficient of assurance (R2) is 0.469. (3) Simultaneously Return On Assets (ROA), Return On Equity (ROE) and Earnings Per Share (EPS) affect stock costs. (4) Partially Return On Assets (ROA) has no impact on stock costs, while Return On Equity (ROE) and Earnings Per Share (EPS) to some extent influence stock costs. Keywords: Return On Assets, Return On Equity, Earnings Per Share And Stock Price